DIVERSITY OF FISH CATCH FISHERMEN IN THE COASTAL AREA OF MENDALOK VILLAGE, SUNGAI KUNYIT SUBDISTRICT, MEMPAWAH REGENCY, KALIMANTAN BARAT - NURUL AINI; WIDADI PADMARSARI SOETIGNYA; INPURWANTO M.SI (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT This study aims to determine the level of diversity of fish caught by fishermen on the coast of the Desa Mendalok. The study used purposive random sampling method by selecting random fishermen based on the fishing gear used, those were 2.5 inch trawl, 7 inch trawl and 3 layer trawl. The study was conducted weekly from September to November 2018. The data collection includes primary data and secondary data. Primary data was obtained from catch fishermen, namely the number and fish species. Secondary data include mendalok village profile, fisheries data marine and fisheries agency of of west Kalimantan Province and rainfall and tides from Meteorological, Climatological and Geophysical Agency. The result showed that there were 35 species fish caught belonging 23 families. The result of this study showed gelama panjang fish (Otolithes ruber), tudung tempayan (Drepane punctata), and bulu ayam fish (Thryssa setirostris) for high frequency fish caught. Sciaenidae and Dasyatidae were the dominant family. Keywords : Type composition, Trawl, Sciaenidae, Dasyatidae